Update of vegetative filter strip scenarios for pesticide risk assessment in Europe - Stefan Reichenberger; Robin Sur; Thorsten Pohlert; Jorge Olivares-Rivas; Katrin Pietsch; Paul Robinson; Rafael Muñoz-Carpena (Science of The Total Environment, 2026)

A heuristic approach to attenuation of non-relevant metabolites in groundwater and drinking water in Germany - Robin Sur; Marco Herrmann; Namjil Ganbaatar; Alexander Singer (Journal of Consumer Protection and Food Safety, 2024)
A simple and effective heuristic approach was developed and validated to predict the concentration of non-relevant metabolites (nrM) of pesticides in groundwater and drinking water resources based on the simulated concentrations in leachate as used in product authorizations. The evaluation of extensive monitoring data for 50 nrM has demonstrated that the heuristic has a high predictive performance, i.e., concentrations of < 10 µg/l in shallow leachate in the unsaturated zone of the soil in 1 m depth are protective of 1 µg/l in groundwater and raw water in 98 % of cases (49/50 nrM). The reason for the excellent predictive power of the heuristic approach is the large concentration attenuation from leachate to groundwater and to raw water, which was determined to be, on average, 25- and 45-fold, respectively.

Exploration of a comprehensive versus a regulatory-oriented modeling framework for field pesticide transport assessment - Dongyang Ren; Feng Pan; Haw Yen; Zhenxu Tang; Robin Sur; Bernard A. Engel (Science of The Total Environment, 2024)

Runoff mitigation on agricultural fields via micro-dams – Literature review and derivation of runoff curve number reductions - Stephan Sittig; Robin Sur (Environmental Research, 2023)

GeoAPEX-P, A web-based, spatial modeling tool for pesticide related environmental assessment - Feng Pan; Qingyu Feng; Haw Yen; Dongyang Ren; Zhenxu Tang; Robin Sur; Jingqiu Chen; Bernard A. Engel (Environmental Modelling & Software, 2023)

Dynamic prediction of effective runoff sediment particle size for improved assessment of erosion mitigation efficiency with vegetative filter strips - Stefan Reichenberger; Robin Sur; Stephan Sittig; Sebastian Multsch; Álvaro Carmona-Cabrero; J. Javier López; Rafael Muñoz-Carpena (Science of The Total Environment, 2023)

Conducting groundwater monitoring studies in Europe for pesticide active substances and their metabolites in the context of Regulation (EC) 1107/2009 - Anne Louise Gimsing; Jutta Agert; Nicole Baran; Arnaud Boivin; Federico Ferrari; Richard Gibson; Lisa Hammond; Florian Hegler; Russell L. Jones; Wolfram König; Jenny Kreuger; Ton van der Linden; et al. (Journal of Consumer Protection and Food Safety, 2019)